Cyberbullying during COVID-19 lockdowns: Prevalence, predictors, and outcomes for youth - António, R.; Guerra, R.; Moleiro, C. (Current Psychology, 2024)
The COVID-19 pandemic posed additional challenges to the safety and well-being of young people who were forced to engage in online learning, spending more time than ever online, and cyberbullying emerged as a notable concern for parents, educators, and students. Two studies conducted online examined the prevalence, predictors, and outcomes of cyberbullying episodes during the lockdowns due to the outbreak of COVID-19 in Portugal. Study 1 (N = 485) examined the prevalence of cyberbullying among youth during the first lockdown period in 2020, focusing on predictors, symptoms of psychological distress and possible buffers of the effects of cyberbullying. Study 2 (N = 952) examined the prevalence of cyberbullying, predictors, and symptoms of psychological distress during the second lockdown period in 2021. Results revealed that most participants experienced cyberbullying, symptoms of psychological distress (e.g., sadness and loneliness) during the lockdowns were higher for those who experienced than for those who did not experience cyberbullying, and those who experienced cyberbullying with higher levels of parental and social support showed lower levels of symptoms of psychological distress (i.e., suicidal ideation). These findings contribute to the existing knowledge on online bullying among youth, specifically during COVID-19 lockdowns.